Technology of Intensive Planting of Sunflower and Soybean for Grain in Sandy Soils (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
The article describes the possibilities of growing grain crops by cultivating sunflower and soybean crops in the conditions of sandy soils of the desert region.